Efficient catalyst development for deep aerobic photocatalytic oxidative desulfurization: recent advances, confines, and outlooks. Issue 4 (2nd October 2022) - Shafiq, Iqrash; Shafique, Sumeer; Akhter, Parveen; Abbas, Ghulam; Qurashi, Ahsanulhaq; Hussain, Murid
ABSTRACT: The supply of environmentally friendly petroleum products has extreme importance in ensuring a reliable healthy climate globally. The elimination of obstinate sulfur complexes is an enormous task in the current challenging legislative situation for fuel refining companies. The conversion of these obstinate sulfur complexes is challenging in the progression of deeper photocatalytic oxidative desulfurization. As an eco-friendly, inexpensive and non-lethal oxidant with bountiful accessibility, oxygen prevailing in the air is utilized in the deep photocatalytic oxidative desulfurization process as a reliable substitute for hydroperoxide and other expensive hydroperoxide derivatives. However, the superlative activation of oxygen under light irradiations is hitherto a challenge. This potential review critically analyzes the recent strategies employed for the development of efficient materials for the progression of deep aerobic photocatalytic oxidative desulfurization system for the removal of obstinate sulfur complexes. Furthermore, the associated technologies influencing the deep photocatalytic oxidative desulfurization performances have been identified and significant parameters for the process optimization are evaluated to address the forthcoming challenges. Graphical Abstract: uf0001